Muscle strength and quality of life in patients with childhood cancer at early phase of primary treatment - Deisenroth, Anne; Söntgerath, Regine; Schuster, Anne Judith; Busch-Hartwig, Christine von; Huber, Gerhard; Eckert, Katharina; Kulozik, Andreas; Wiskemann, Joachim (Pediatric hematology and oncology, 2016)
Cancer- and treatment-related side effects in patients with childhood cancer may cause limitations in motor performance affecting activities of daily living (ADLs). Data focusing on long-term effects are available, but little is known with regard to the short-term perspective. Therefore, the purpose of this study was to assess muscle strength performance and quality of life (QoL) in children and adolescents with cancer at the beginning of primary treatment. Forty children and adolescents aged 5-18 years (mean: 11.39 ± 4.08 years) with different types of childhood cancer were enrolled. On average 36 ± 20.5 days after diagnosis, strength performance in 7 muscle groups was assessed by handheld dynamometry. KINDL questionnaires were completed to evaluate QoL (children's self-report and parents' report). All parameters were compared with age- and gender-matched reference values. Patients with childhood cancer showed significantly lower strength values in all muscle groups (P < .01) compared with age- and gender-matched controls. Most affected were the lower extremities, with a −57.1% ± 10.4%, median: −59.2%, minimum: −75.4%, maximum: −41.4% percentage deviation in knee flexion from healthy peers. Children themselves and parents assessed total QoL significantly below age- and gender-matched reference values (P < .01). Correlation between elbow flexion and self-reported QoL was detected. Broader correlations were found for the parents' report. Muscle weakness and decreased QoL in children and adolescents seem to persist already at the beginning of anticancer treatment. This underlines the need of counteracting measures, such as exercise intervention programs, starting as early as possible during the treatment process. Efforts on this topic are currently being carried out by our group.
Gesehen am 07.06.2020